The role of robotic assisted laparoscopy in early stage cervical cancer, the danish experience. (1st November 2019) - Schnack, TH; Jensen, PT; Bjørn, SF; Frøding, L; Ketabi, Z; Jochumsen, K; Fuglsang, K; Dinesen, J; Soegaard, CH; Soegaard-Andersen, E; Jensen, MM; Oester, LH; et al.
Abstract : Introduction/Background: Since the introduction of robotic assisted laparoscopy it has been the preferred surgical approach for early stage cervical cancer (ECC) in the Nordic countries. Lately, a randomized trial comparing open access vs. minimal invasive surgery has questioned the oncological safety of robotic surgery in ECC. The aim of the present study was to evaluate the safety of robotic surgery in the treatment of ECC in Denmark. Methodology: Clinical and follow-up data on all consecutive patients with ECC stage IA2-IB1 who underwent radical hysterectomy in the period January 1st 2005 - June 30th 2017 were derived from the Danish Gynecologic Cancer Database (DGCD). Data was validated with other registers and patient files. Descriptive statistics with univariate and multivariate analyses were used. Results: 1125 ECC patients were included; 530 who underwent a radical hysterectomy before the introduction of robotic-assisted laparoscopy (period 1) and 595 who underwent surgery after the introduction of robotic-assisted laparoscopy (period 2). No significant differences in the rate of recurrence, recurrence location, or use of chemo-radiation between the two cohorts was observed. Furthermore, no significant differences in the five-year cancer specific survival between cases diagnosed before and after the introduction of robotic-assisted laparoscopy was found - five year cancer specific survivals of 94.1% and 95.9% (p-value=0.10) in period 1 and period 2, respectively. Conclusion: Based on national and prospectively collected data our cohort study found no indication that the oncologic safety such as risk of recurrence and survival has been compromised by the introduction of the robotic platform. However, use of robotic surgery for early cervical cancer will be followed closely throug our national cancer database (DGCD) in the future. Disclosure: Nothing to disclose.